REVIEW ON THE CORONAVIRUS DISEASE (COVID-19) PANDEMIC: ITS OUTBREAK AND CURRENT STATUS - Kalambe, Avdhoot; Joshi, Kimaya; Jadhav, Asha Sambhaji; Ramyasri, Adapally; Lahamge, Devidas (IJRDO-Journal of Applied Science, 2023)
The first incidence of the COVID-19 pandemic, which is spreading quickly, was found in Wuhan, Hubei Province, China, in December 2019. On March 11, 2020, the WHO proclaimed COVID-19 to be a pandemic due to the rapid increase in cases both in China and around the world. The disease, which mostly damages the lung parenchyma, is spread through respiratory droplets produced when infected individuals cough or sneeze. Patients with COVID-19 can experience a wide range of clinical symptoms, from asymptomatic infections to life-threatening disease. Although COVID-19 patients are most frequently affected by respiratory involvement, the virus can also harm other organ systems. The development of extra-pulmonary symptoms affecting the gastrointestinal, cardiovascular, hematological, renal, musculoskeletal, and endocrine systems is explained by the systemic inflammation caused by the disease in combination with multisystem expression of Angiotensin Converting Enzyme 2 (ACE2), a receptor that permits viral entry into cells. In this article, we’ve covered the wide body of literature on COVID-19 that covers a variety of clinical presentations according on the organ system affected as well as clinical presentations in certain populations like kids, pregnant women, and patients with impaired immune systems. Additionally, we briefly touched on the treatment of COVID-19. Understanding the various clinical manifestations can aid doctors in correctly diagnosing COVID-19 early on and implementing the necessary countermeasures to stop the disease’s progress.